An improvement on capacitive properties of clew-like MnO2 by thermal treatment under nitrogen. (3rd August 2017) - Sun, Yin; Huang, Naibao; Sun, Xiannian; Wang, Dongchao; Zhang, Junjie; Qiao, Shaoming; Gao, Zhaoqing
Abstract: The clew-like MnO2, synthesized by a low-temperature liquid-phase reaction, were thermally treated (300–700 °C) under nitrogen atmosphere to improve its capacitive properties. Crystal structure, porosity, conductivity, microstructure and the electrochemistry properties of thermal treated under nitrogen MnO2 electrode were measured. The result indicates that thermal treatment under nitrogen can improve MnO2 electrode's capacitive properties and the maximum specific capacitance is 368.2 F/g at 1 A/g in a 6 mol/L KOH electrolyte for the prepared electrode annealed at 400 °C, which was increased by 102.4% compared with untreated sample (181.9 F/g). Further observation of MnO2 electrode's microstructure showed that oxygen deficiency-induced phase transformation during thermal treatment under nitrogen leads to co-existence of multivalent Mn, which could improve its electrical conductivity and surface properties, then enhancing its electrochemical performance. Highlights: Oxygen deficiencies of MnO2 produced by thermal treatment under nitrogen atmosphere. Oxygen deficiencies can enhance the capacitive properties of MnO2 electrode. The highest specific capacitance of prepared MnO2 electrode is 363.75 F/g at 1 A/g. Excellent capacitance characteristics: 102.4% capacitance increase after treatment.